Three new physalins from Physalis alkekengi var. franchetii - Xu, Wan-Xuan (Springer Berlin Heidelberg, 2013)
Three new physalin steroids, physalin III (1), physalin IV (2), 3-O-methylphysalin X (3), together with five known physalins (4–8) were isolated from the 80% EtOH extract of calyces of Physalis alkekengi var. franchetii. The structures of the new compounds were revealed through 1D and 2D NMR and mass spectroscopic studies. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-013-0021-z and is accessible for authorized users.